Paleodiversity of Late Cretaceous Ankylosauria from Mexico and their phylogenetic significance - Rivera-Sylva, Héctor E.; Stinnesbeck, Wolfgang (Swiss journal of palaeontology, 2018)
Isolated bones and osteoderms of ankylosaurian dinosaurs recovered from Late Cretaceous sediments of northern Coahuila, northeastern Mexico, have been identified as remains of nodosaurids. Here, we summarize these discoveries and provide a review on Mexican Ankylosauria from a taxonomic perspective. We also present a new taxon, Acantholipan gonzalezi gen. et sp. nov. from the Pen Formation and provide a phylogenetic analysis integrating the new taxon. A. gonzalezi is the first named ankylosaur from Mexico that adds to the currently rare nodosaurid diversity from southern Laramidia.